2005
DOI: 10.1097/01.blo.0000192033.50316.bf
|View full text |Cite|
|
Sign up to set email alerts
|

Blood Salvage and Allogenic Transfusion Needs in Revision Hip Arthroplasty

Abstract: Therapeutic study, Level IV (case series). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 14 publications
4
24
1
1
Order By: Relevance
“…Goulet et al [2] found that transfusion requirements were decreased when Cell Saver was used in orthopedic procedures. McMurray et al [1] and Garvin et al [11] found that Cell Saver decreased the need for donor blood transfusion in primary and revision hip arthroplasty. Cell Saver has also been shown to decrease the amount of other blood transfusions in children undergoing acetabuloplasty [12].…”
Section: Discussionmentioning
confidence: 99%
“…Goulet et al [2] found that transfusion requirements were decreased when Cell Saver was used in orthopedic procedures. McMurray et al [1] and Garvin et al [11] found that Cell Saver decreased the need for donor blood transfusion in primary and revision hip arthroplasty. Cell Saver has also been shown to decrease the amount of other blood transfusions in children undergoing acetabuloplasty [12].…”
Section: Discussionmentioning
confidence: 99%
“…Garvin et al could show that the need for ABT using two different systems for CATS was reduced in cases of hip revision by 31 % [44]. Zarin et al found decreased perioperative blood loss using CATS for patients with revision of femoral and acetabular components or only the acetabular component [23].…”
Section: Discussionmentioning
confidence: 99%
“…Garvin et al [12] reported total blood loss was greatest for femoral revision than for acetabular revision in 147 patients undergoing revision THA. Zarin et al [29] reviewed the records of 126 patients undergoing revision THA and found the greatest blood loss occurred when both components were revised, while the blood loss when only one component was revised was not different between femoral component revision and acetabular revision.…”
Section: Discussionmentioning
confidence: 99%